The Principal's Managerial Role in Implementing Inclusive Education to Improve School Quality - Varietasari, Dian; Soedjono, Soedjono; Kusumaningsih, Widya (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the role of the principal as a manager in organizing inclusive education at SD Negeri 14 Mulyoharjo, Pemalang Regency. The research focuses on how managerial functions, planning, organizing, actuating, and controlling, are implemented to support inclusive education and improve school quality. A qualitative research approach with a case study design was employed. The data for this study consist of primary data obtained from key informants, including the principal, teachers, and school committees, selected through purposive sampling, as well as secondary data derived from school documents such as work plans, curriculum adaptations, and evaluation reports. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed using an interactive model comprising three concurrent flows of activity: data reduction, data display, and conclusion drawing or verification. The findings reveal that the principal plays a crucial role in systematically managing inclusive education through comprehensive planning based on student needs assessment, effective organization of human resources and inclusive teams, continuous guidance for teachers, and regular supervision. Furthermore, the integration of digital technology and collaboration with external institutions strengthens inclusive practices. The results indicate that effective managerial leadership contributes significantly to creating an inclusive school culture and improving overall educational quality. Therefore, the principal’s managerial competence is a key factor in ensuring the sustainability of inclusive education. This study provides practical implications for school leaders and policymakers in optimizing inclusive education management in primary schools.